Haematocrit in elite athletes - Vergouwen, P. C.; Collee, T.; Marx, J. J. (International Journal of Sports Medicine, 1999)
It is possible to increase haemoglobin (Hb) and haematocrit (Ht) to non-physiological values by injecting recombinant human erythropoietin (rhEPO). Although this treatment may result in a better performance of athletes, it may also cause a health risk. To prevent doping with rhEPO, the Union Cycliste Internationale has decided to exclude male cyclists with Ht>0.50 and female cyclists with Ht>0.47 from competition. These cut-off values, however, may result in a non-justified exclusion of clean athletes. To test this hypothesis, we measured the Ht of elite athletes (50 men and 41 women) during a total study period of 43 months. Ht was compared with that in healthy control subjects (134 men and 144 women). No significant differences in Ht were detected between male elite athletes and their references and female elite athletes and their references (P>0.05). In both populations, however, male subjects were found with Ht>0.50, 6 controls and 5 elite athletes (4 highlanders and 1 lowlander). In the female subjects 5 controls but not one of the athletes exceeded a Ht>0.47. "Increased" Ht values among athletes were mainly seen in highlanders. The study shows that it is very difficult to set up a decision value for Ht with regard to doping by erythropoietin.